2020
DOI: 10.5194/acp-20-5457-2020
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of nitrous acid to the atmospheric oxidation capacity in an industrial zone in the Yangtze River Delta region of China

Abstract: Abstract. A suite of instruments was deployed to simultaneously measure nitrous acid (HONO), nitrogen oxides (NOx = NO + NO2), carbon monoxide (CO), ozone (O3), volatile organic compounds (VOCs – including formaldehyde, HCHO) and meteorological parameters near a typical industrial zone in Nanjing in the Yangtze River Delta (YRD) region of China from 1 to 31 December 2015. High levels of HONO were detected using a wet-chemistry-based method. HONO ranged from 0.03 to 7.04 ppbv with an average of 1.32±0.92 ppbv. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 99 publications
3
28
0
1
Order By: Relevance
“…Limited studies have related to AOC changes with O 3 formation. Recent studies modeled the highest ever-reported concentrations of OH at urban site in the YRD ( Zheng et al, 2020 ; Zhu et al, 2020 ), which indicates AOC is strong in this region. Therefore, it is necessary to study the changes of AOC due to NO x emission and O 3 elevation during the COVID-19 lockdown period.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Limited studies have related to AOC changes with O 3 formation. Recent studies modeled the highest ever-reported concentrations of OH at urban site in the YRD ( Zheng et al, 2020 ; Zhu et al, 2020 ), which indicates AOC is strong in this region. Therefore, it is necessary to study the changes of AOC due to NO x emission and O 3 elevation during the COVID-19 lockdown period.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies on AOC only focused on radical chemistry ( Keywood et al, 2004 ; von Sonntag, 2007 ; Xue et al, 2016 ; Zheng et al, 2020 ). Limited studies have related to AOC changes with O 3 formation.…”
Section: Introductionmentioning
confidence: 99%
“…But it is slightly higher than most observations in other southern China (2.1−5.6) ppb (Guo et al, 2016;Wang et al, 2017;Yang et al, 2019;Zeng et al, 2019b) and the background NCP region (3.5−3.7 ppb) conducted 3−6 years before our experiments (Yang et al, 2017;Wang et al, 2020). The HCHO photolysis rate of 8.3×10 6 molec cm -3 s -1 at noon on pollution days is higher than pervious results in a suburban site of Beijing during winter (~6.7×10 6 molec cm -3 s -1 at noon) (Tan et al, 2018) and an industrial zone of southeastern China during winter (1.6×10 6 molec cm -3 s -1 averaged over 7:00−16:00) (Zheng et al, 2020). This indicates that high reactive VOC emissions over the NCP region can drive fast photochemistry in cold seasons on a regional scale by acting as radicals in addition to precursors.…”
Section: Impacts Of Radicals On Rapid Increase Of Panmentioning
confidence: 82%
“…The ratio of HONO to NOx or the ratio of HONO to NO2 have been extensively applied to indicate heterogeneous conversion of NO2 to HONO (Li et al, 2012b;Liu et al, 2019c;Zheng et al, 2020). Compared with the HONO/NO2 ratio, the HONO/NOx ratio can better avoid the influence of primary emissions (Liu et al, 2019c).…”
Section: Instrumentationmentioning
confidence: 99%